2022
DOI: 10.1016/j.ctcp.2021.101530
|View full text |Cite
|
Sign up to set email alerts
|

Reiki practitioners’ perceptions of the impact of the COVID-19 pandemic on the experience, practice and future of Reiki

Abstract: Objectives This study examined the impact of the COVID-19 pandemic on the experience, practice and future of Reiki in the UK, including the personal impact of the pandemic on practitioners and their work, practitioner perceptions of the future of the profession and Reiki delivery, and practitioner experiences and views of distant Reiki in comparison to hands on or near the body treatments. Method A qualitative study using semi-structured interviews was carried out with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
0
2
0
4
Order By: Relevance
“…Çakra tıkanıklığı oluştuğunda diyabet, organlarda hastalıklar ve bağımlılık gelişmektedir. (32)(33)(34)36,37) Dördüncü Çakra (Kalp Çakrası/ Yeşil veya Pembe renk): Göğüslerin ortasındadır. Sevginin ve ilişkilerin enerji merkezidir.…”
Section: Reiki' Nin Tarihçesiunclassified
See 3 more Smart Citations
“…Çakra tıkanıklığı oluştuğunda diyabet, organlarda hastalıklar ve bağımlılık gelişmektedir. (32)(33)(34)36,37) Dördüncü Çakra (Kalp Çakrası/ Yeşil veya Pembe renk): Göğüslerin ortasındadır. Sevginin ve ilişkilerin enerji merkezidir.…”
Section: Reiki' Nin Tarihçesiunclassified
“…Çakra tıkanıklık durumunda akciğer kanseri, damar tıkanıklıkları, fibrokistler, kalp ve bağışıklık sistemiyle ilgili hastalıklar görülebilir. (19,32,36,37) Yaşam Boyu Hemşirelik Dergisi & Journal of Life Long Nursing www:llnursing.com -editor@llnursing.com 237 Beşinci Boğaz Çakrası (Açık Mavi): Çakra iletişim, ifadeler ve isteklerin ana enerji merkezidir. Tiroid ve paratiroid hormonlarının salınımını etkiler.…”
Section: Reiki' Nin Tarihçesiunclassified
See 2 more Smart Citations
“…A qualitative study with ten Reiki practitioners in the UK reported that they saw value in adapting their practice by using technology and distance Reiki but believed that distance Reiki could not replace in-person practice. 38 While many studies support in person Reiki for mental and physical health outcomes, less is known about the effects of distance Reiki. To date, 7 studies on distance Reiki have been conducted which have shown benefits to psychological health, but mixed results with respect to pain.…”
Section: Introductionmentioning
confidence: 99%